(untitled) (Castilla. Estudios de Literatura, 2017)
This work studies the relations between literature and photography in the story “Ambros Adelwarth” (The Emigrants) of W.G. Sebald from a socio-historical perspective, from the studies of trauma, memory and image, and attending to the consciousness of this combination. Sebald, next to the current of German documentary realism, proposes with his work a management of the memory conformed dialectically by the assembly of oral and written testimony and of photographic image. His use of the imagination supposes a surpassing of the time of each means and questions the concepts of identity, reality and fiction.